Calpain inhibitor AK 295 inhibits calpain-induced apoptosis and improves neurologic function after traumatic spinal cord injury in rats - Çolak, Ahmet; Kaya, Mehmet; Karaoğlan, Alper; Sağmanlıgil, Ayhan; Akdemir, Osman; Şahan, Elife; ÇELİK, ÖZGE (Soc Espanola Neurocirugia, C/O Dr Poza, Gran Via Salzillo 42, 30005 Murcia, Spain, 2009)
Background. An increase in the level of intracellular calcium activates the calcium-dependent neutral protease calpain, which in turn leads to cellular dysfunction and cell death after an insult to the central nervous system. fit this study, we evaluated the effect of a calpain inhibitor, AK 295, on spinal cord structure, neurologic function, and apoptosis after spinal cord injury (SCI) in a murine model. Methods. Thirty albino Wistar rats were divided into 3 groups of 10 each: the sham-operated control group (group 1), the spinal cord trauma group (group 2), and the spinal cord trauma plus AK 295 treatment group (group 3). After having received a combination of ketamine 60 mg/kg and xylazine 9 mg/kg to induce anesthesia, the rats in groups 2 and 3 were subjected to thoracic trauma by the weight drop technique (40 g-cm). One hour after having been subjected to that trauma, the rats in groups 2 and 3 were treated with an intraperitoneal injection of either dimethyl sulfoxide 2 mg/kg or AK 295 2 mg/kg. The effects of the injury and the efficacy of AK 295 were determined by an assessment of the TUNEL technique and the results of examination with a light microscope. The neurologic performance of 5 rats from group 2 and 5 from group 3 was assessed by means of the inclined plane technique and the modified Tarlov's motor grading scale 1, 3, and 5 days after spinal cord trauma. Findings. Light-microscopic examination of spinal cord specimens from group 2 revealed hemorrhage, edema, necrosis, and vascular thrombi 24 : hours after trauma. Similar (but less prominent) features were seen in specimens obtained from group 3 rats. Twenty-four hours after injury, the mean apoptotie cell numbers in groups I and 2 were zero and 4.57 +/- 0.37 cells, respectively. In group 3, the mean apoptotic cell number was 2.30 +/- 0.34 cells, a value significantly lower than that in group 2 (P < .05). Five days after trauma, the injured rats in group 2 demonstrated significant motor dysfunction (P < .05). In comparison, the motor scores exhibited by group 3 rats were markedly better (P < .05). Conclusions. AK 295 inhibited apoptosis via calpain-dependent pathway's and provided neuroprotection and improved neurologic function in a rat model of SCI. To our knowledge, this is the first study to evaluate the use of AK 295, a calpain inhibitor, after SCI. Our data suggest that AK 295 might be a novel therapeutic compound for the neuroprotection of tissue and the recovery of function in patients with a SCI.
Keywords: AK 295; apoptosis; calpain inhibitor; secondary damage; spinal cord trauma; activated neutral proteinase; crystal-structure; down-regulation; calcium; brain; calpastatin; expression; neuroprotection; degradation; mechanism; apoptoz; ikincil hasar; omurilik travması; aktive nötr proteinaz; kristal yapı; kalsiyum; beyin; nöro; mekanizma; bozulma